Bioaccumulation of emerging contaminants in aquatic food chains and its implications for public health - Paul, Dr. Priya; Pandey, Dr. Anamika (International Journal of Aquatic Research and Environmental Studies, 2025)
Emerging contaminants (ECs), including per- and polyfluoroalkyl substances (PFAS), pharmaceuticals and personal care products (PPCPs), micro- and nanoplastics, novel flame retardants, pesticide metabolites, and other substances that have entered the environment, pose ecological and human health problems. They remain in water and exhibit complex behaviors that facilitate the accumulation of organisms and the magnification of other organisms at higher trophic levels. Accumulation of ECs in primary producers and invertebrates, and in higher-trophic-level freshwater, estuarine, and marine ecosystem animals such as fish and marine mammals, has been documented across all three ecosystem types. Human exposure occurs through the consumption of contaminated seafood, with some mixtures exceeding risk thresholds for endocrine disruption, immunotoxicity, and developmental impacts. Subsistence fishers and coastal communities with high seafood consumption are the most exposed and thus most vulnerable. This review aims to consolidate what is known about the mechanisms of distribution and the health implications of ECs' bioaccumulation, assess exposure assessment and analytical consistency data gaps, and identify regulatory and research gaps to better protect public health through monitoring, regulation, and research.
Keywords: Bioaccumulation, Biomagnification, PFAS, Pharmaceuticals, Microplastics, Trophic transfer, Risk assessment